Anti-TNFα agents curb platelet activation in patients with rheumatoid arthritis. Issue 8 (27th January 2016) - Manfredi, Angelo A; Baldini, Mattia; Camera, Marina; Baldissera, Elena; Brambilla, Marta; Peretti, Giuseppe; Maseri, Attilio; Rovere-Querini, Patrizia; Tremoli, Elena; Sabbadini, Maria Grazia; Maugeri, Norma
Abstract : Background: Cardiovascular disease is important in rheumatoid arthritis (RA). Tissue factor (TF) is expressed upon platelet activation and initiates coagulation. Anti-tumour necrosis factor-α (TNFα) agents seem to decrease RA-associated cardiovascular events. We investigated whether (1) TNFα activates human platelets and (2) TNFα pharmacological blockade modulates the platelet-leucocyte reciprocal activation in RA. Design: The expression of platelet TNFα receptors has been assessed by flow cytometry and immunogold electron microscopy. Platelet and leucocyte activation has been assessed also in the presence of antibodies against the TNFα receptors 1 and 2 and of infliximab. TF expression, binding to fibrinogen and phosphatidylserine exposure, has been assessed by flow cytometry, TF activity by coagulation time and by endogenous thrombin generation. Markers of platelet and leucocyte activation have been assessed in 161 subjects: 42 patients with RA, 12 with osteoarthritis, 37 age-matched and sex-matched patients with chronic stable angina and 70 age-matched and sex-matched healthy subjects. Results: TNFα elicited the platelet activation and the expression of TF, which in turn prompted thrombin generation and clot formation. Inhibition of the TNFα-induced activation restricted platelet ability to activate leucocytes and to induce leucocyte TF. TNFα inhibition did not influence platelet activation induced by collagen, ADP or thrombin receptor activating peptide-6. Platelets of patients with RA were more activated than those of controls. Activation was reduced in patients treated with TNFα inhibitors. Conclusions: TNFα-dependent pathways control platelet activation and TF expression in RA. Further studies will verify whether the protective effect of TNFα inhibitors on cardiovascular events involves their ability to modulate platelet function.